PERSEPSI MAHASISWA TERHADAP PELAKSANAAN KEGIATAN PENGALAMAN LAPANGAN INDUSTRI (PLI) DI DUNIA USAHA/ INDUSTRI PROGRAM STUDI S1 DAN D3 TATA BUSANA JURUSAN KESEJAHTERAAN KELUARGA FT UNP - Hafsah, Siti; Yasnidawati, Yasnidawati; Adriani, Adriani (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study is a descriptive research with quantitative approach that aims to describe the perception of students S1 and D3 Fashion Design Family Welfare Department towards the implementation of Field Experience Industry (PLI) in the business/industry. The population in this study is all of the students S1 and D3 Fashion Design has implemented PLI from July to Desember 2012 and from January to June 2013 amounted to 37 people, samples were taken from all populations. Data processing is doing by determining the percentage and categorization. The result of the research showed student’s perception of S1 and D3 Fashion Design Family welfare of the PLI observation activities in the business/industry are in the unfavorable category (63,9%), in planning activities in the business/industry that are in well enough category (74,9%), the pre-production activities are in well enough category (79,9%), whereas the production activities are in the unfavorable category (64,2%), perception of students S1 and D3 Fashion Design on the implementation of PLI in the business/industry well enough (70,1%). For that the students needs to encreas the ebility and skill of student in order to engage in any activity’s PLI in the business/industry. Kata kunci: Persepsi, Kegiatan Pengalaman Lapangan Industri (PLI)